(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This paper explores the methodological significance of integrating visual resources into Foreign Language Teaching (FLT) to enhance the speaking skills and communicative competence of students. In modern pedagogy, bridging the gap between passive linguistic knowledge and active verbal production remains a primary challenge. This study highlights the cognitive and psychological advantages of using picture-based materials, categorizes effective classroom techniques, and provides practical recommendations for structuring interactive speaking activities in higher education.